PERFORMANCE AND ECONOMIC BENEFITS OF BROILER CHICKEN PRODUCTION USING WHITE SORGHUM AS REPLACEMENT FOR MAIZE - Jama’a, N. A.; Sani, A.; Sale, A. S.; Doma, U. D. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study was conducted at the Teaching and Research Farm of the Abubakar Tafawa Balewa University Bauchi. Five diets were formulated in which white sorghum replaced maize at 0, 25, 50, 75 and 100 % in diets 1, 2, 3, 4 and 5 respectively. Two hundred (200) day old broiler chicks were used for the research. After brooding, the chicks were randomly allotted to the five diets in four replicates each with ten (10) chicks per replicate in a completely randomised design. Experimental feeds and water were supplied ad libitum and all other routine activities as well as vaccinations against New castle diseases were carried out according to schedule. Data on initial weights, daily feed intake and body weight changes were taken during the eight weeks’ period of the feeding trial. Feed conversion ratio and feed efficiency were calculated from the relationships of feed intakes and weight gains. Data generated were subjected to analysis of variance. The results obtained showed no significant difference on all the performance parameter studied at both the starter and finisher phases. However, at starter phase, the highest initial body weight was found on diet (1264.59g) and the lowest was found on diet 5 (252.08g). Daily feed intake ranged from 74.48 g on diet 3 to 81.30 g on diet 5. Daily weight gain values ranged from 23.66g on diet 1 to 25.45g on diet 5. The feed conversion ratio ranged from 3.13 on diet 4 to 3.22 on diet 1. Similarly, in finisher phase. The final weight gain ranged from 1622.41 g on diet 4 to 1797.30 g on diet 2. The daily feed intake ranged between 23.38 g on diet 1 to 31.26 g on diet 2. The best feed conversion ratio was obtained on diet 3 (2.82) while the poorer was obtained on diet 4 (3.18). Numerical values for daily feed intake were between 78.32 g on diet 3 to 86.16 g on diet 5. Daily weight gain which ranged from 26.04g on diet 4 to 27.84 g on diet 2 are statistically similar. Feed conversion ratio ranged from 2.99 on diet 3 to 3.31 on diet 5. The lowest feed cost was found on diet 5 (₦ 305.61) and the highest on diet 3 (₦ 319.68). The highest total feed cost was found on diet 4 (₦ 1194.11) and the lowest on diet 5 (₦ 1289.66). Feed cost per kilogram gain was higher on diet 5 (₦ 969.67) and the lowest on diet 1 (₦ 923.38). It was concluded that white sorghum can completely replace maize in broiler chicken diets without affecting the general performance of the birds. It is therefore recommended for use in broiler chicken diets.